2001
DOI: 10.1007/s002130100921
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tricyclic antidepressants and selective serotonin re-uptake inhibitors on handwriting movements of patients with depression

Abstract: The results suggest either that TCAs have adverse effects on motor functioning or that they are less effective in the treatment of motor retardation than SSRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…However, these effects have to be confirmed in another study, since Tucha et al (2002) did not find any significant differences between patients with depression taking SSRIs and healthy controls regarding kinematical parameters of handwriting. The latter finding must be interpreted with caution because Tucha et al (2002) did not examine the effects of depressive psychomotor retardation on automated hand movements in patients off antidepressants and during their subsequent treatment.…”
Section: Reboxetine (N=12)mentioning
confidence: 52%
See 3 more Smart Citations
“…However, these effects have to be confirmed in another study, since Tucha et al (2002) did not find any significant differences between patients with depression taking SSRIs and healthy controls regarding kinematical parameters of handwriting. The latter finding must be interpreted with caution because Tucha et al (2002) did not examine the effects of depressive psychomotor retardation on automated hand movements in patients off antidepressants and during their subsequent treatment.…”
Section: Reboxetine (N=12)mentioning
confidence: 52%
“…Fleminger 1992;Sachdev and Aniss 1994;Lemelin and Baruch 1998;Sabbe et al 1999;Caligiuri and Ellwanger 2000;Mergl et al 2004); however, only few studies focused on the effects of antidepressant drugs on psychomotor function (e.g. Lader et al 1986;Kerr et al 1996;Hindmarch 1997), with kinematical analysis of hand movements being rarely applied in this context (Sabbe et al 1997;Tucha et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Handwriting is a highly skilled, coordinated motor activity. In previous research, handwriting movements have frequently been shown to be a sensitive measure of the effects of pharmacological agents Tucha et al 2002). High densities of nicotinic cholinergic receptors have been identified in areas related to the control and execution of movements and the speed component of tasks measuring psychomotor functioning such as tapping speed (West and Jarvis 1986) or motor reaction time (LeHouezec et al 1994;Houlihan et al 1996) appear to be sensitive to nicotine-induced improvements.…”
Section: Introductionmentioning
confidence: 98%